Characterisation of the Aerodynamic Aerosol Classifier Transfer Function for Particle Sizes up to 5 Micrometres - Simon D. Payne; Tyler J. Johnson; Jonathan P. R. Symonds (Aerosol and Air Quality Research)
Abstract The Aerodynamic Aerosol Classifier (AAC) classifies particles with the desired aerodynamic diameter by generating opposing centrifugal and drag forces on the particles using rotating concentric cylinders and a clean sheath flow. Particle transmission through the classifier is described by its transfer function, which is an important indicator of classifier performance. Characterisation of the classifier’s transfer function improves the accuracy of its common aerosol applications, such as measuring particle size distributions or providing classified particles to other aerosol instruments for calibration or further analysis. This characterisation is commonly achieved experimentally using a tandem set-up of the same classifier. While this approach was previously used to characterise the AAC’s transfer function for particle aerodynamic diameters up to 2.4 µm using a nebuliser and a Condensation Particle Counter (CPC), the current study expands the AAC’s characterisation up to 5 µm using a condensation aerosol generator and an Optical Particle Counter (OPC). This upper size range is significantly higher than that offered by other common aerosol classifiers, such as the approximate 1 µm upper limit typical of the Differential Mobility Analyser (DMA), and it is well suited to many applications, including OPC calibration, bio-aerosols, drug delivery and inhalation studies, and atmospheric dust analysis. This study found that the AAC maintains its high transmission efficiency (≥ 60%) for particles up to 5 µm and that its transfer function width factor increases (i.e., the distribution becomes narrower) as the aerodynamic diameter increases. Setpoint agreement between two different production AACs remained within 2% over the size range tested. Therefore, the AAC has excellent performance for classifying particles up to 5 µm.